Strategies for the Adaptive Reuse of the Former Monastery of Saint Augustine in Vicopelago - Martina Bosone; Silvia Iodice (In_Bo, 2021)
The theme of the reuse of disused religious cultural heritage has been the focus of attention in the national and international debate for years. The vastness and importance of this heritage, a connotation element of the landscape and of the life of the communities born around it, highlights with extreme urgency the open question on its future and therefore on the identification of strategies consistent with the complex of values of which it is bearer. The different approaches adopted in cases of reuse already carried out showed the strengths and weaknesses of the implemented processes and drew attention to the need to identify shared guiding criteria for the development of an exportable but also adaptable methodology to different contexts. The summer school “New scenarios for disused monastic heritages. Lucca cases between monastic memories and Puccini's legacy” represented an opportunity for fruitful interdisciplinary debate to deepen the theme of the reuse of religious cultural heritage from both a theoretical-cognitive and practical-operational perspective. Starting from the study of some good practices, the experimentation on the case study of the former Monastery of Sant’Agostino in Vicopelago (Lucca) led to the development of various project proposals that were presented to local stakeholders, as the first outcome of the studies conducted and as the first step in the structure conversion process.